THE RESISTANCE OF PEOPLE IN PAPUA (1945-1962) - Lumintang, Onie M. (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2009)
This article discusses a sequence of events showing the resistance of the people of Papua since 1945 until 1965. This resistance was conducted by the movement figures of Papua who were aggressively struggling for the independence of Indonesia or claiming the independence for the land of Papua. This Movement was conducted in various areas with different resistance targets and forms.